A revision of the extra-Andean Vivianiaceae - Ferreira, João Paulo Ramos; Hassemer, Gustavo; Campestrini, Sérgio; Weigend, Maximilian; Trevisan, Rafael (Phytotaxa, 2016)
The extra-Andean species of Vivianiaceae are here reviewed. We examine the morphological circumscription of Viviania albiflora (=Caesarea albiflora), evaluating all synonyms listed for this species. Although V. albiflora is a highly polymorphic species, especially regarding leaf morphology, a detailed morphological analysis leads us to conclude that V. linostigma, previously considered as one of its synonyms, needs to be accepted as a species. We noticed that the two species could be reliably differentiated by a trait such as tetramerous flowers for V. linostigma versus pentamerous flowers for V. albiflora. We present the other morphological characters and distribution differences that distinguish it from V. albiflora. All known synonyms of V. albiflora as well as V. linostigma along with the types lost at B herbarium are lectotypfied. An identification key, descriptions, illustrations and lists of synonyms are presented.